DISTRIBUIÇÃO ESPACIAL E ACESSO A SERVIÇOS PÚBLICOS ESSENCIAIS EM POLÍTICAS DE HABITAÇÃO DE INTERESSE SOCIAL - Manuela Maria Nascimento (Universidade Federal do Maranhão, 2017)
This research evaluatesthe housing provision in the scope of the availability of education and health public services for populations relocated to housing estates, as well as their spatial distribution in the Recife city, predominantly conditioned to determinations of political and economic origin. In thiscontext, it may be questioned: Does the housing policy it is contrary to the right to the city, taking into account its spatial distribution and deficiencies in the management of the increase in the demand for essential public services? In the search for answers, it was made a bibliographic and documentary review, direct observation and analysis through geoprocessing. It was verified that the implantation of the housing estates is not accompanied by an improvement in the distribution of the education and health services, being conditioned by political decisions of a financial nature and not by the increase of the social demand.